1989
DOI: 10.1056/nejm198903023200903
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Bone Mass in Daughters of Women with Osteoporosis

Abstract: To determine whether premenopausal daughters of women with postmenopausal osteoporosis have lower bone mass than other women of the same age, we measured the bone mineral content of the lumbar spine and femoral neck and midshaft, using dual-photon absorptiometry, in 25 postmenopausal women with osteoporotic compression fractures and in 32 of their premenopausal daughters; we then compared the results with those in normal controls. As compared with normal postmenopausal women, women with osteoporosis had lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
113
3
6

Year Published

1991
1991
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 561 publications
(133 citation statements)
references
References 11 publications
11
113
3
6
Order By: Relevance
“…In addition, the studies have shown that the genetic effects on BMD are not constant throughout the skeleton. It was well known that the genetic and environmental contribution to bone mass differed according to skeletal site, as shown by the lower genetic effect on hip BMD than spine BMD, both in twin [8]and mother-daughter [10]models. In accordance, the VDR alleles had a weak effect at the neck of the femur, a predominantly cortical bone site, and a stronger effect at the lumbar spine, a predominantly trabecular bone site.…”
Section: Vitamin D Receptor Genementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the studies have shown that the genetic effects on BMD are not constant throughout the skeleton. It was well known that the genetic and environmental contribution to bone mass differed according to skeletal site, as shown by the lower genetic effect on hip BMD than spine BMD, both in twin [8]and mother-daughter [10]models. In accordance, the VDR alleles had a weak effect at the neck of the femur, a predominantly cortical bone site, and a stronger effect at the lumbar spine, a predominantly trabecular bone site.…”
Section: Vitamin D Receptor Genementioning
confidence: 99%
“…Hormones are variables presenting physiologic and pathologic variations, whereas nutrition and exercise may positively or negatively influence the process. The genetic regulation of bone mass acquisition has been known for many years, resulting from studies in families with a high incidence of osteoporosis, in monozygotic (MZ) or dizygotic (DZ) twins, or on inter-racial differences [7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17]. Possible candidate genes implicated in such a regulation have been discussed over the last decade and a certain number of associations between candidate gene polymorphisms and variations in BMD have been described [18, 19, 20, 21, 22, 23, 24, 25](table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Type I osteoporosis is apparently triggered by the transient acceleration of bone loss that occurs with the fall in estrogen levels in women at menopause. Several reports suggest that the disease is familial (1,2,4).…”
mentioning
confidence: 99%
“…As bone loss is associated with aging, investigators have reasoned that people who have fractures and low bone density probably have lost more bone mass than people who do not have fractures [11,12,13]. This hypothesis may be correct, but an alternative explanation may be true as well: people with fractures may have achieved a lower peak bone mass as young adults and subsequently lost bone mass at the same rate as the rest of the population [14]. …”
Section: Introductionmentioning
confidence: 99%